Penganekaragaman dan Penyeragaman dalam Aktivitas Nelayan Pulau Sembilan: Sebuah Penjelasan Prosesual dan Kontekstual - Munsi Lampe (Antropologi Indonesia, 2009)
This article describes and explains the complexity of dynamic process of sea fishery in Pulau Sembilan since the ancient up to now. With the application of the concepts such as diverging, homogenizing, continuity, and temporal, it has been found that the complexity of dynamic process of the fishing economy has oscillated between divergence and homogeneity. The divergence refers to different kinds of fishing activities based on various fish species by different traditional catch techniques, on the other hand, homogeneity refers to the concentration of fishermen activities on one or more similar kinds of fishing activities such as catching life fish (kerapu, sunu, napoleon) and life lobster as top commodities in the period of 1990s. When the populations of the main fish species were decreased as negative impact of overexploitation since the beginning of the 2000s, there were many fishermen returning again to different kinds of fishing activities. It means that the diverging process began its era. The process of diverging and homogenizing of fishery involve cognitive systems as guide for fishermen decision making. These processes indicate persistent and temporal functions of traditional and new fishing techniques of Pulau Sembilan fishing communities. By processual and contextual explanation, it was clear that diverging and homogenizing of fishery is a continuum of its dynamic process. The processes are influenced by internal and external socio-cultural factors and the change of sea physical environment and natural resource conditions. From this explanation known that new practice of using potassium cyanide contributes significantly to the serious degradation of large part of coral reef zones in and outside of Pulau Sembilan water. Key words: Coral reef resource use, diverging and homogenizing, continuity and temporal functions.